Determining Sustainability of a community midwifery model in Siaya County, Kenya. - Syagga, Edwinah; Estambale, Benson (Numid Publishers, 2018)
Introduction: Reducing maternal mortality requires coordinated, long-term efforts. Sustainable Development Goal 3 (SDG3) states that “by 2030, reduce the global maternal mortality ratio (MMR) to less than 70 per 100,000 live births”. One of the key indicators for monitoring the progress towards meeting the MMR target is the proportion of births attended by skilled birth attendants. One strategy to achieve this was the implementation of community midwifery. This study aimed at finding out whether the community midwifery practiced in Siaya County was sustainable. Methods: A cross-sectional study that used both quantitative and qualitative data in four sub-counties of Siaya County. The study involved facilities as well as sampled mothers who had given birth within the previous year and who were served by the four sampled health facilities. It also involved skilled birth attendants working at the health care facilities of the primary levels of the health care system as well as the community Health Visitors (CHVs) attached to the selected health care facilities. Findings: Current practice that involved the community participation improved the skilled attendance. This would ensure sustainability due to model’s affordability and acceptance by the community members as evidenced by their acceptability and satisfaction with the midwives’ services. Conclusion: The CHVs may be relied upon to promote skilled birth attendance at the primary level of the health system as well as refer the women to the health facilities for childbirth, thus reducing the burden of employing more expensive and trained personnel in the community, thereby making community midwifery services cheaper for the County health system and community to afford. Recommendations: Community midwifery model, as practiced in Siaya County should be stepped up with the support of the County Department of Health.
Keywords: Community midwifery; Sustainability; Skilled birth attendance